Metode Evaluasi Praktis untuk Peningkatan Berkelanjutan pada Proses Pengisian produksi - Asmaul Fauziah; Fitriani Endang Wahyu; Winantari Agnes Nuniek (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to utilize Overall Equipment Effectiveness (OEE) analysis as a diagnostic framework to identify and map the root causes of performance losses in critical cream filling machinery within a cosmetics manufacturing company in East Java, recognizing that fragmented or piecemeal approaches to evaluating machine performance often fail to capture the interrelated sources of production inefficiency. The research was conducted over a three-month period using a descriptive quantitative method through direct observation of filling machine operations. The collected data included machine operating time, downtime, production output, and defective units. In this study, OEE was applied not merely as a performance indicator but as a loss-based diagnostic tool capable of systematically revealing hidden inefficiencies affecting equipment effectiveness. The results show that OEE values fluctuated significantly between 20.31% and 90.51%, with monthly averages of 71.12%, 80.62%, and 61.29%, respectively. While the quality component remained relatively stable at above 98%, substantial variations were observed in availability and performance due to machine downtime and reduced operating speeds. Further analysis using the Six Big Losses framework identified setup and adjustment time and idling or minor stoppages as the dominant contributors to decreased machine effectiveness, confirming that the filling machine functions as a critical production bottleneck whose instability directly influences production continuity. These losses collectively accounted for the majority of production interruptions and performance deterioration throughout the observation period. The findings underscore the importance of systematically reducing the Six Big Losses to stabilize and improve OEE. Implementing preventive maintenance, minimizing setup time variability, and strengthening operational discipline are therefore essential steps for achieving sustainable improvements in machine effectiveness and overall production efficiency.